Adaptive response to wine selective pressures shapes the genome of a Saccharomyces interspecies hybrid. Issue 8 (27th August 2021) - Lairón-Peris, María; Castiglioni, Gabriel L.; Routledge, Sarah J.; Alonso-del-Real, Javier; Linney, John A.; Pitt, Andrew R.; Melcr, Josef; Goddard, Alan D.; Barrio, Eladio; Querol, Amparo
Abstract : During industrial processes, yeasts are exposed to harsh conditions, which eventually lead to adaptation of the strains. In the laboratory, it is possible to use experimental evolution to link the evolutionary biology response to these adaptation pressures for the industrial improvement of a specific yeast strain. In this work, we aimed to study the adaptation of a wine industrial yeast in stress conditions of the high ethanol concentrations present in stopped fermentations and secondary fermentations in the processes of champagne production. We used a commercial Saccharomyces cerevisiae × S. uvarum hybrid and assessed its adaptation in a modified synthetic must (M-SM) containing high ethanol, which also contained metabisulfite, a preservative that is used during wine fermentation as it converts to sulfite. After the adaptation process under these selected stressful environmental conditions, the tolerance of the adapted strain (H14A7-etoh) to sulfite and ethanol was investigated, revealing that the adapted hybrid is more resistant to sulfite compared to the original H14A7 strain, whereas ethanol tolerance improvement was slight. However, a trade-off in the adapted hybrid was found, as it had a lower capacity to ferment glucose and fructose in comparison with H14A7. Hybrid genomes are almost always unstable, and different signals of adaptation on H14A7-etoh genome were detected. Each subgenome present in the adapted strain had adapted differently. Chromosome aneuploidies were present in S. cerevisiae chromosome III and in S. uvarum chromosome VII–XVI, which had been duplicated. Moreover, S. uvarum chromosome I was not present in H14A7-etoh and a loss of heterozygosity (LOH) event arose on S. cerevisiae chromosome I. RNA-sequencing analysis showed differential gene expression between H14A7-etoh and H14A7, which can be easily correlated with the signals of adaptation that were found on the H14A7-etoh genome. Finally, we report alterations in the lipid composition of the membrane, consistent with conserved tolerance mechanisms.